Contribution of the Bony Bankart in Calculating Glenoid Bone Loss. Issue 5 (May 2023) - Bozzo, Isabella; Kooner, Paul; Nelson, Ralph; Marwan, Yousef; Paruthikunnan, Samir; Laverdière, Carl; Boily, Mathieu; Martineau, Paul A.
Background: Determining the magnitude of glenoid bone loss in patients with anterior shoulder instability is an important step in guiding management. Most calculations to estimate the bone loss do not include the bony Bankart fragment. However, if it can be reduced and adequately fixed, the estimation of bone loss may be decreased. Purpose: To derive a simple equation to calculate the surface area of the bony fragment in Bankart fractures. Study Design: Case series; Level of evidence, 4. Methods: A total of 26 patients suspected of having clinically significant bone loss underwent computed tomography imaging preoperatively, and the percentage of glenoid bone loss (%BL) was approximated with imaging software using a freehand region of interest area measurement with and without the inclusion of the bony Bankart fragment. By assuming this bony fragment as a hemi-ellipse with height, H, and thickness, d, we represented the surface are of the bony piece (A bone fragment = π Hd 4 ), and subtracted it from the overall %BL. They compared this value with the one found using imaging software. Results: Without the inclusion of the bony Bankart, the overall %BL by the standard true-fit circle measured using imaging software was 23.8% ± 9.7%. When including the bony Bankart, the glenoid %BL measured using imaging software was found to be 12.1% ± 8.5%. The %BL calculated by our equation with the bony Bankart included was 10% ± 11.1%. There was no statistically significant difference between the %BL values measured using the equation and the imaging software ( P = .46). Conclusion: Using a simple equation that approximates the bony Bankart fragment as a hemiellipse allowed for estimation of the glenoid bone loss, assuming that the fragment can be reduced and adequately fixed. This method may serve as a helpful tool in preoperative planning when there are considerations for incorporating the bony fragment in the repair.